Real-World Implementation of Precision Psychiatry: A Systematic Review of Barriers and Facilitators - Baldwin Helen; Loebel-Davidsohn Lion; Oliver Dominic; de Pablo Gonzalo S; Stahl Daniel; Riper Heleen; Fusar-Poli Paolo (MDPI, 2022)
Background: Despite significant research progress surrounding precision medicine in psychiatry, there has been little tangible impact upon real-world clinical care.
Objective: To identify barriers and facilitators affecting the real-world implementation of precision psychiatry.
Method: A PRISMA-compliant systematic literature search of primary research studies, conducted in the Web of Science, Cochrane Central Register of Controlled Trials, PsycINFO and OpenGrey databases. We included a qualitative data synthesis structured according to the 'Consolidated Framework for Implementation Research' (CFIR) key constructs.
Results: Of 93,886 records screened, 28 studies were suitable for inclusion. The included studies reported 38 barriers and facilitators attributed to the CFIR constructs. Commonly reported barriers included: potential psychological harm to the service user (n = 11), cost and time investments (n = 9), potential economic and occupational harm to the service user (n = 8), poor accuracy and utility of the model (n = 8), and poor perceived competence in precision medicine amongst staff (n = 7). The most highly reported facilitator was the availability of adequate competence and skills training for staff (n = 7).
Conclusions: Psychiatry faces widespread challenges in the implementation of precision medicine methods. Innovative solutions are required at the level of the individual and the wider system to fulfil the translational gap and impact real-world care.